Beneficial Effects on Brain Micro-Environment by Caloric Restriction in Alleviating Neurodegenerative Diseases and Brain Aging - Zhang, Li; Xu, Huachong; Ding, Ning; Li, Xue; Chen, Xiaoyin; Chen, Zhuangfei (Frontiers in Physiology, 2021)
Aging and neurodegenerative diseases are frequently associated with the disruption of the extracellular microenvironment, which includes mesenchyme and body fluid components. Caloric restriction (CR) has been recognized as a lifestyle intervention that can improve long-term health. In addition to preventing metabolic disorders, CR has been shown to improve brain health owing to its enhancing effect on cognitive functions or retarding effect on the progression of neurodegenerative diseases. This article summarizes current findings regarding the neuroprotective effects of CR, which include the modulation of metabolism, autophagy, oxidative stress, and neuroinflammation. This review may offer future perspectives for brain aging interventions.